Active tunable terahertz bandwidth absorber based on single layer graphene. (1st April 2023) - Li, Wenxin; Yi, Yingting; Yang, Hua; Cheng, Shubo; Yang, Wenxing; Zhang, Huafeng; Yi, Zao; Yi, Yougen; Li, Hailiang
Abstract: In this paper, an active tunable terahertz bandwidth absorber based on single-layer graphene is proposed, which consists of a graphene layer, a photo crystal plate, and a gold substrate. When the Fermi energy ( E f ) of graphene is 1.5 eV, the absorber shows high absorption in the range of 3.7 THz–8 THz, and the total absorption rate is 96.8%. By exploring the absorption mechanism of the absorber, the absorber shows excellent physical regulation. The absorber also shows good adjustability by changing the E f of graphene. This means that the absorber exhibits excellent tunability by adjusting the physical parameters and E f of the absorber. Meanwhile, the absorber is polarization independent and insensitive to the incident angle. The fine characteristics of the absorber mean that the absorber has superior application value in many fields such as biotechnology and space exploration.